High Chromosomal Reorganization and Presence of Microchromosomes in Chactidae Scorpions from the Brazilian Amazon - Bruno Almeida; Stella Malcher; Marlyson Costa; Jonas Martins; Rudi Procópio; Renata Noronha; Cleusa Nagamachi; Julio Pieczarka (Biology, 2023)
Scorpions are of particular interest in cytogenomic studies, as they can present a high incidence of chromosomal rearrangements heterozygous in natural populations. In this study, we cytogenetically analyzed four species of Chactidae. In Brotheas, 2n = 40 was observed in Brotheas silvestris, 2n = 48 in Brotheas paraensis, and 2n = 50 (cytotype A) or 2n = 52 (cytotype B) among populations of Brotheas amazonicus. Our results showed a bimodal karyotype in Neochactas parvulus, 2n = 54, with microchromosomes and a concentration of constitutive heterochromatin in macrochromosomes. The 45S rDNA is located in only one pair of the karyotype, with different heteromorphisms of clusters of this rDNA in the cytotype B of B. amazonicus, with NOR-bearing chromosomes involved in multi-chromosomal associations during meiosis I. The U2 snDNA was mapped in the interstitial region of distinct karyotype pairs of three Chactidae species. Our results indicate the possible formation of cryptic species in B. amazonicus; the different 45S rDNA configurations in the genome of this species may result from amplification and degeneration. We suggest that the bimodal karyotype in N. parvulus results from fusion/fission events and that the unequal distribution of repetitive DNAs between macro and microchromosomes contributes to the maintenance of its asymmetry.